EVALUASI KEANDALAN SISTEM DISTRIBUSI PADA PENYULANG CEKO (FEEDER 3) GARDU INDUK PANGKALPINANG PLN AREA BANGKA - Dedi Syah Putra; Wahri Sunanda; Rudy Kurniawan (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2015)
One of main components in the electric generation system is distribution system. it have function, distribute the energy to customers more continuously and well. To evaluate it reliability for feeder 3 in PLN Area Bangka before and after using SCADA seized by reliability of distribution SAIDI, SAIFI, and CAIDI system index. The test result based on sample of SAIDI, SAIFI, and CAIDI index before using SCADA method at 2013 is 2,77 time/year for SAIFI index, 6,21 hours/year for SAIDI index, and 2,242 hours/year for CAIDI index. Meanwhile for after using SCADA method at 2014 is 10,32 time/year for SAIFI index, 19,18 hour/year for SAIDI index, and 1,858 hours/year for CAIDI index.